2018
DOI: 10.21276/apalm.2300
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Relationship Between Hypothyroidism and Platelet Parameters Including Platelet Indices, Platelet Distribution Width, Plateletcrit and P-LCR

Abstract: Searching the recent literature revealed that thyroid dysfunction is related to fibrin formation and fibrinolysis. Few studies proposed that there was an increase in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Vagdatli et al and De Luca et al reported that PDW is a more specific platelet activation marker and provides more information than MPV. 22,23 A similar study done by Khemka et al 24 found no significant difference between the hyperlipidemic patient and their PDW. One study in the literature investigated the relationship between PDW and carotid intima-media thickness, and that study did not reveal a correlation between carotid intima-media thickness and PDW.…”
Section: Discussionmentioning
confidence: 79%
“…Vagdatli et al and De Luca et al reported that PDW is a more specific platelet activation marker and provides more information than MPV. 22,23 A similar study done by Khemka et al 24 found no significant difference between the hyperlipidemic patient and their PDW. One study in the literature investigated the relationship between PDW and carotid intima-media thickness, and that study did not reveal a correlation between carotid intima-media thickness and PDW.…”
Section: Discussionmentioning
confidence: 79%